Utilization of leonardite and coal bottom ash for production of ceramic floor tiles - Namkane K. (2017)
© 2017, Springer-Verlag GmbH Germany. The aim of this research was to exploit leonardite and coal bottom ash (CBA), which are waste products from coal power plants, for investigating their potential as raw materials in the production of ceramic floor tiles. The developments of ceramic body were mixed with traditional raw materials. Different proportions of ceramic materials were studied in order to explore the proper composition with a variety of wastes containing leonardite and coal bottom ash from 20% up to 80%. Unglazed tiles were produced by shaping through dry pressing and single firing. The physical, chemical, and mechanical properties of the samples were investigated. The total waste (CBA and leonardite) contained in the production was close to 42.8%, and it presented properties that are adequate for it to be classified in groups within the ISO 13006 standard, and yielded the highest flexural strength which enabled the obtained ceramic floor tile bodies to satisfy the requirement to be classified in group BIIa. The chemical resistances of the products were classified in the category UA group which passed the minimum requirement for classification as chemical attack, set by standard EN 14411.